2003
DOI: 10.1242/jcs.00662
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial inflammation: the role of differential expression of N-deacetylase/N-sulphotransferase enzymes in alteration of the immunological properties of heparan sulphate

Abstract: Heparan sulphate N-deacetylase/N-sulphotransferase (NDST) enzymes catalyse the reaction that initiates sulphation and subsequent modification of the oligosaccharide, heparan sulphate (HS). The extent and distribution of sulphate substitution on HS plays a vital role in regulation of the binding of a range of proteins, including IFN-γ, several interleukins and most chemokines. In this study, the expression of NDST transcripts was found to be non-uniform between a range of cell types, suggesting that different c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 50 publications
3
47
0
Order By: Relevance
“…One reason for the induction of CXCL8 binding to HSPGs could involve soluble mediators, such as tumor necrosis factor. This cytokine, which is present in the RA joint (54), is known to increase HS sulfation and enhance binding of the chemokine CCL5 to cultured human microvascular endothelial cells (55).…”
Section: Discussionmentioning
confidence: 99%
“…One reason for the induction of CXCL8 binding to HSPGs could involve soluble mediators, such as tumor necrosis factor. This cytokine, which is present in the RA joint (54), is known to increase HS sulfation and enhance binding of the chemokine CCL5 to cultured human microvascular endothelial cells (55).…”
Section: Discussionmentioning
confidence: 99%
“…5 Recent work from our group has shown that the availability of chemokine-binding motifs can depend on changes in the expression of sulfotransferase enzymes, such as N-deacetylase/Nsulfotransferase-1. 52 Hence, chemical microheterogeneity within the cell surface heparan sulfate population provides a possible explanation for the focal accumulation of MCP-1.…”
Section: Competition Of Cell Surface Mcp-1 Binding By Heparinmentioning
confidence: 99%
“…Thus, we turned our attention to the analysis of GAG fine structure and selected biosynthetic enzymes responsible for this fine structure. The failure of Northern blotting to detect different GAG synthesizing enzymes [31], suggests that the messages encoding these biosynthetic enzymes are either expressed at low levels or are rapidly turned over. RT-PCR has proven to be a powerful method for the sensitive detection of mRNA levels [28,29,30].…”
Section: Discussionmentioning
confidence: 99%
“…These enzymes are encoded by two genes and afford the first blocks of N-sulfation upon which other enzymes act. Thus, the content of N-sulfo groups profoundly impact subsequent downstream modification of HS by Osulfotransferases [10,31]. NDST-1 mRNA expression increases during pre-eclampsia, a possible sign of inflammation.…”
Section: Discussionmentioning
confidence: 99%